Reviews - Philip Barker; Anne Brown; Alison Holmes (Association for Learning Technology, 2002)
The user guide consists of a 28-page A5 format brochure. It gives an overview (4 pages) of the contents of the CD-Rom and how it can assist in the writing process in three main sections: core skills, writing for science and writing for advocacy. Within each of these subsections more detail is provided, with the authors giving a short introductory aim for each task and the expected outcomes